Quranic Epistemology of Abdullah Darraz on His Critic of Morality: A Study of the Book Dustūr al-Akhlāq fī Al-Qur’ān - Ma'arif, Cholid; Zarkasyi, Amal Fathullah; Mukaromah, Kholila (IAIN Ponorogo, 2024)
This paper reveals descriptively the textual basis of Muhammad Abdullah Darraz’s thoughts as stated in his work Dustūr al-Akhlāq fī al-Qur’ān: Dirāsah Muqāranah li al-Akhlāq al-Nażāriyyāt fī al-Qur’ān. It aims to confirm the extent of the text analysis model used by Darraz in formulating the concept of Islamic morality. The researcher used a qualitative research type and a content analysis approach by tracing the interpretation of the verses of the Koran and the background to the criticism built by Darraz. This research makes Dustūr al-Akhlāq fī al-Qur’ān a material object and the critic of morality as a formal object. The fīndings are as follows: Fīrst, in his thought project, Darraz uses Qur’anic epistemology by indirectly using al-Ghazali’s maqāṣīd al-Qur’ān method. So, with this method, he succeeded in finding forms of commands in various pronunciations of the Qur’an to confīrm the Shari'ah of overall morality. Second, Darraz proved that Islamic morality differs from Western morality based on empiricism and is not value-free. This is preceded by constructive criticism of the existing Islamic treasures and their further development. On the other hand, it applies destructive criticism to Western views on morality. In short, Darraz's thought project is an anti-thesis effort to the conventional concept of morality that has developed by offering an original reference to understanding the Koran.